Pathogen surveillance (Leptospira spp., Rotavirus, Hepatitis E virus and Norovirus) in a wild golden-headed lion tamarin (Leontopithecus chrysomelas) population from an urban Atlantic Forest park in Niterói, Rio de Janeiro, Brazil - Molina, Camila Vieira (2018)
Most nonhuman primates are distributed throughout tropical countries, most of all in Brazil. However, half of the Brazilian endemic species live in areas where deforestation rates are over 90%. The world currently faces severe biodiversity losses caused by anthropogenic activities such as deforestation, pollution, introduction of exotic species, habitat fragmentation, and climate changes all consequences of the rising of agriculture, livestock and urbanization; a great risk for wild animal species. The golden-headed lion tamarin (GHLT; Leontophitecus chrysomelas) is an endangered species that became invasive in an exotic forested area in Niterói, Rio de Janeiro state, Brazil. The initially few invasive GHLT individuals became hundreds, adapted to living in proximity to humans and domestic animals, frequently found inside houses, digging garbage, crossing streets and in open sewers. These GHLTs were captured as part of a conservation project; some animals were translocated to Bahia state, in southern Brazil, an area within the species original range, whiel the remaining individuals were kept in captivity. Disease ecology in altered environments is still poorly understood; however, these GHLTs likely had contact with many pathogens. Therefore, the present study aimed on surveying this population for possible pathogens: Leptospira spp., Rotavirus A, Norovirus GI and GII, and Hepatitis E virus 3 HEV 3. A total of 939 serum samples from 593 GHLTs were tested for 21 Leptospira serovars, resulting in three positive sera samples from two GHLTs: one for serovar Shermani and one for serovar Hebdomadis. Molecular methods (PCR) were employed on 100 kidney samples from animals that died in captivity due to other reasons: only one sample was positive for a saprophytic Leptospira. Fecal pools from 101 family groups were all negative for RNA RT-PCR (Rotavirus A, Norovirus GI and GII, and HEV 3). Our findings suggest that the epidemiological importance of such pathogens in this GHLT population is either low or non-existent. These results are unexpected and surprising considering the intensely altered environment and biology observed in this GHLT population. These data are important to understand the local disease ecology, as well as to evaluate the efficiency of the translocation project, with the final goal of performing future studies to compare our data with those obtained from the translocated animals.